NAFLD: a sign of “early aging”? - Rastamanesh, Reza; Catanzaro, Roberto; Sollano, Josè; Marotta, Francesco (Acta Biomedica Atenei Parmensis, 2014)
To te Editor,Hamaguchi and colleagues very recently reported aging a risk factor for non-alcoholic fatty liver disease (NAFLD) in premenopausal women, independent of ...